Synthesis and Characterization of MoS2 Films for PEC cells - T., Joseph Sahaya Anand (Penerbit Universiti Kebangsaan Malaysia, 2009)
Molybdenum Disulfide (MoS2) is a VI – VI compound semiconductor has hexagonal structure useful for high temperature lubricant. Polycrystalline films are electrodeposited cathodically on tin oxide (SnO2) coated conducting glass substrates. The deposited films are characterized by various techniques includes the X-ray diffraction analysis, where the structure of the films is identified as hexagonal and the lattice parameters are a = b = 3.153 Å and c = 12.279 Å which are in good agreement with standard report values. From optical analysis, the bandgap value is calculated as 1.68 eV with indirect bandgap nature. From scanning electron micrographs it is found to be the surface appears are comparatively granular with grains in irregularly shaped. The thickness of the MoS2 films was calculated in the region 0.80 – 0.82 m by using weight gain method. From Mott-Schottky plots the films are found to be n-type and the semiconductor parameters of the film are derived. From the photoelectrochemical cell studies the fill factor, open circuit voltage, short circuit current and efficiency are calculated.